Pelatihan Desain Kemasan dan Perhitungan Harga Jual untuk Produk UMKM Desa Salo Palai - Cahyadi, Dwi; Azizah, Amiril; Andansari, Dita; Wulaningrum, Ratna; Arifin, Zainal; Diah, Ahyar M.; Irawan, Dedy; Utomo, Karyo Budi; Suparno, Suparno; Keliwar, Said (Jurnal ETAM, 2025)
Salo Palai Village is one of the villages in Kutai Kartanegara Regency, East Kalimantan. Salo Palai Village has several garden products such as pepper and other processed garden products such as banana chips, fruit syrup and so on. With garden products and processed garden products, this village has the potential to be able to develop the welfare of its community through MSMEs from several of these products. As an MSME business that continues to grow, good packaging and calculating the selling price of MSME products are things that should be considered in attracting and introducing their products to consumers in order to increase the value and number of sales of their products. By conducting lecture methods and direct training to participants, it will have a direct impact on them on how to design good packaging and promotions for MSMEs. Thus, community service activities in the field of design and promotion through financial calculations for product sales are expected to be an effort to provide an understanding of the importance of increasing sales value.